ISOLATION AND IDENTIFICATION OF Pasteurella multocida From Farm Animals - كاظم سراب; صالح ضحى; شبر اسماعيل (Iraqi Journal of Science, 2024)
This study was carried out for isolation of Pasteurella multocida from sheep and goat and identification by using biochemical and morphological characterization. On hundred eighty five samples included (nasal swabs blood and infected lungs) from animals with respiratory infection ,and from normal animals, were collected for this purpose. Twelve isolates of P.multocida were identified by using biochemical and morphological characterization total isolation was (7.6%) from sheep, and (3%) from goats .All isolates are susceptible for penicillin and chlormphenical , while other antibiotic like Cephalothin, Amigacin, Amoxicillin, Impicilin, Tetracycline,and Trimetheprium, show a different level of susceptibility consequently as well as this study shows that there are a different level of resistant for Gentamicin,Streptomycin,and Lincomycin. Gentamicin,Streptomycin,and Lincomycin.